Association Between Sex Hormones and Visual Field Progression in Women With Primary Open Angle Glaucoma: A Cross-Sectional and Prospective Cohort Study - Qiu, Yichao; Yu, Jian; Tang, Li; Ren, Jun; Shao, Mingxi; Li, Shengjie; Song, Yunxiao; Cao, Wenjun; Sun, Xinghuai (Frontiers in Aging Neuroscience, 2021)
Purpose: We evaluated the level of sex hormones in female patients with primary open angle glaucoma (POAG) to determine whether they are associated with the onset and/or progression of POAG. Methods: The cross-sectional study enrolled 63 women with POAG and 56 healthy women as normal control subjects. Furthermore, 57 women with POAG were included and followed-up for at least 2 years in the cohort study. All subjects were evaluated for serum concentration of sex hormones [prolactin (PRL), luteinizing hormone (LH), testosterone (TESTO), follicle-stimulating hormone (FSH), progesterone (PROG), and estrogen (E2)] and underwent visual field (VF) examination. In the cross-sectional study, Spearman analysis, linear regression analysis, and logistic regression analysis were performed to assess risk factors for POAG in women. In the cohort study, Cox regression analyses and Kaplan–Meier survival analysis were performed to identify factors associated with VF progression in women with POAG. Results: In the cross-sectional study, the level of E2 was significantly lower in the POAG group than in the normal group (p < 0.05). Multiple logistic regression showed that the decreased level of E2 was a risk factor of POAG (OR = 0.27, 95% CI = 0.09–0.78, p < 0.05), especially in premenopausal subjects. In the cohort study, there were 29 non-progression subjects and 28 progression subjects. Patients in the progression group had significantly lower levels of E2 than those in the no progression group (p < 0.01). The decreased level of E2 at baseline was associated with POAG progression (HR = 0.08, 95% CI = 0.02–0.46, p < 0.05), especially in premenopausal subjects. Patients with POAG and with lower baseline E2 levels had significantly lower VF non-progression rates than patients with higher E2 levels (log-rank test p < 0.001), especially premenopausal subjects (log-rank test p < 0.05). Additionally, logistic regression analyses, Cox regression analyses, and Kaplan–Meier survival analysis showed that PROG, LH, FSH, and TESTO were risk factors of POAG and/or significantly associated with POAG progression. Conclusion: A decreased E2 level is a POAG risk factor and is associated with VF progression in women with POAG, especially in premenopausal subjects. Additionally, other sex hormones (PROG, LH, FSH, and TESTO) might also play a role in POAG pathogenesis.